CORELATION OF ADVERSE PERINATAL OUT COMES AND PLACENTAL INFARCTS IN HYPERTENSIVE PRETERM PREGNANCIES - Afzal, Ejaz; Sherin, Fatima; Seema, Nighat (Journal of Ayub Medical College Abbottabad, 2015)
Background: The placenta can provides valuable information about the damaging effects of hypertension on pregnancy and foetal outcome. This study was conducted to study the frequency of placental infarcts in hypertensive preterm pregnancies and its effects on foetal outcomes. Methods: This cross-sectional study was conducted at Department of Obstetrics and Gynaecology, Khyber Teaching Hospital, Peshawar and Department of Anatomy, Khyber Medical College, Peshawar from January 2008 to March 2009. The sample size consisted of hundred placentae divided into two groups. Group A consisting of 50 normal full term placentae (delivered between 37-42 weeks of gestation). Group-B consisting of 50 premature placentae from hypertensive mothers (35-37 weeks of gestation). The data was collected on a pre-designed Performa and analysis was done by SPSS-17. Results: In the placentae of premature group the incidence of placental infarcts were increased. Foetal outcome was poor in the presence of placental infarcts. Conclusion: Adverse perinatal outcomes including growth restriction and still birth is higher in hypertensive premature deliveries with placental infarcts than in normal full term deliveries.